2007
DOI: 10.1088/0954-3899/34/8/s74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jet quenching on hydrodynamical evolution of QGP

Abstract: We study the effects of jet quenching on the hydrodynamical evolution of the quark-gluon plasma (QGP) fluid created in a heavy-ion collision. In jet quenching, a hard QCD parton, before fragmenting into a jet of hadrons, deposits a fraction of its energy in the medium, leading to suppressed production of high-pT hadrons. Assuming that the deposited energy quickly thermalizes, we simulate the subsequent hydrodynamic evolution of the QGP fluid. For partons moving at supersonic speed, vp > cs, and sufficiently la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Another study [51] included expansion of the plasma and used source terms similar to scenario 1. It also concluded that a minimum at δφ = π is hard to achieve.…”
Section: Jet-splitting and The Challenge Of Diffusion Wakesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study [51] included expansion of the plasma and used source terms similar to scenario 1. It also concluded that a minimum at δφ = π is hard to achieve.…”
Section: Jet-splitting and The Challenge Of Diffusion Wakesmentioning
confidence: 99%
“…It is natural for us to hope that a diffusion wake really is generated when a hard parton traverses a quark-gluon plasma, but that it is erased or disguised in the data. More realistic theoretical treatments should include expansion of the plasma, as in [51,52,53] and perhaps also a more sophisticated treatment of hadronization; as compared to the sonic boom, the diffusion wake is deeper inside the expanding medium, so it has more chance to broaden, soften, and thermalize before freeze-out. Some hints of this were observed in [51].…”
Section: Jet-splitting and The Challenge Of Diffusion Wakesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also strongly dependent on jet quenching deposition dE/dx, as demonstrated in Fig.3(a). But mostly it is sensitive to viscosity: since the conical flow has larger gradients 10 It does not matter whether hydro is or is nor linearized: thus Chaudhuri and Heinz [46] could not possibly resolve the issue as well, they just made an arbitrary selection. The only approach which does not have this problem is AdS/CFT, to be discussed below.…”
Section: The Conical Flow: Excitation Of Two Modesmentioning
confidence: 99%
“…Theoretically, the latter is described by Quantum Chromodynamics (QCD) [1,2]. After the collisions, the system evolves hydrodynamically, cooling and becoming more diluted until it reaches the instant of thermal freeze-out τ , where the system decouples, and the hadronic particles do not interact any more [3,4]. The QGP state of matter can be explored by investigating the final hadrons, especially those created in hard processes whose trajectories traverse the entire system [5].…”
Section: Introductionmentioning
confidence: 99%